2003
DOI: 10.1046/j.1475-1313.2003.00158.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between intraocular pressure and refractive error adjusting for age and central corneal thickness

Abstract: Our results confirm the positive association between IOP and increasing degrees of myopia. This finding would support the hypothesis that the relationship between glaucoma and myopia might be pressure mediated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 24 publications
5
43
0
3
Order By: Relevance
“…Simultaneously, our study found that when at accommodation-relaxed status, the IOPs of progressing myopes and emmetropes were not significantly different. This result was consistent with some previous studies, 11,12 but different from others. 8,10 That might be because factors influencing IOP values were very complicated (eg, central corneal thickness, corneal curvature, measuring time point, and measuring position of subjects [26][27][28][29] ) and different studies used various research methods.…”
Section: Changes Of Intraocular Pressure and Myopia L Yan Et Alsupporting
confidence: 92%
See 1 more Smart Citation
“…Simultaneously, our study found that when at accommodation-relaxed status, the IOPs of progressing myopes and emmetropes were not significantly different. This result was consistent with some previous studies, 11,12 but different from others. 8,10 That might be because factors influencing IOP values were very complicated (eg, central corneal thickness, corneal curvature, measuring time point, and measuring position of subjects [26][27][28][29] ) and different studies used various research methods.…”
Section: Changes Of Intraocular Pressure and Myopia L Yan Et Alsupporting
confidence: 92%
“…9,[11][12][13] Some researchers 9,11 reported a significant association between IOP and myopia progression, whereas others 12,13 found no certain relationship between them. However, unlike the uncertainty of the relationship between static IOP values and myopia progression, IOP variations had been demonstrated to cause refraction and AL changes in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Shiose (1984Shiose ( , 1990 indicated that IOP is positively correlated with blood pressure (BP), obesity and other cardiac risk variables, but negatively with age. Intraocular pressure has been positively correlated with body mass index (BMI) after adjusting for age, gender and BP (Mori et al 2000), and also with increasing degrees of myopia after adjusting for age, central corneal thickness (CCT) and other related factors (Nomura et al 2004). However, these previous studies carried out in Japan measured IOP using non-contact tonometry (NCT), which has relatively low accuracy and is more likely to be affected by CCT than is Goldmann applanation tonometry (GAT) (Moseley et al 1989;Rouhiainen & Terasvirta 1990;Mackie et al 1996;Recep et al 2001;Tonnu et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have attempted to identify risk factors associated with higher IOP (Armaly 1967;Colton & Ederer 1980;Klein & Klein 1981;Shiose 1984Shiose , 1990David et al 1987;Shiose et al 1991;Sommer et al 1991;Klein et al 1992;Leske et al 1997;Bonomi et al 1998;Nomura et al 1999Nomura et al , 2002Nomura et al , 2004Mori et al 2000;Hashemi et al 2005;Lin et al 2005;Mitchell et al 2005;Nakano et al 2005;Xu et al 2005;Suzuki et al 2006). It is well known that IOP increases with age ) the other important risk factor for glaucoma ) among Black, White and Iranian populations (Armaly 1967;Colton & Ederer 1980;Klein & Klein 1981;David et al 1987;Klein et al 1992; Leske et al 1997;Bonomi et al 1998;Hashemi et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Myopia, a very common condition in Japan [21], is often accompanied by higher IOPs [22][23][24][25][26], abnormal optic nerve head morphology [27][28][29], parapapillary atrophy [30], thin lamina cribrosa [31], and impaired retinal microcirculation [32,33]. All of these factors are closely associated with the development of glaucoma, and myopia has been considered an important risk factor for the development and progression of POAG [7,13,25,[34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%